The repercussions of the eutrophication phenomenon on human health and welfare / Siti Nur Shazwani Shukor … [et al.] - Shukor, Siti Nur Shazwani; Abdul Aziz, Nur Syawanie; Jamaludin, Siti Nur Syifaa; Noor Hisham, Aida Qasrina; Nurshahirah, Rahizar; Abd Malek, Alyssa Safiyah; Hisham, Nur Hafizah; Kamaruddin, Sharir Aizat; Hashim, Aimie Rifhan (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Eutrophication of water bodies is a peculiar environmental phenomenon and has become more prevalent, primarily because excessive input of nutrients into a watershed. Agriculture run off treated wastewater discharge from sewage treatment facilities, lawn fertilizers, and any other organic wastes, all contribute to this problem. In most cases, it encourages the growth of algae and other aquatic plants, resulting in harmful algae blooms (HABs), leading to a deterioration of quality and condition of natural waters, mostly in marine or coastal ecosystems.